Structural Change Effect of Institutions Quality: Empirical Evidence From Developing Countries. - Dianda, Issa; Zidouemba, Patrice Rélouendé; Traoré, Fié Faiçal (American Journal of Economics & Sociology, 2025)
We investigate the heterogeneous effects of institutional quality on structural change across 88 developing countries from 2000 to 2018. For our empirical analysis, we employ ordinary least squares, two‐stage least squares, quantile regressions, and the generalized method of moments. Our findings reveal that higher institutional quality promotes structural change, with a particularly pronounced effect in countries at the lower end of the structural transformation spectrum. While all dimensions of institutions quality contribute to structural change, their impacts vary: economic institutions (government effectiveness and regulatory quality) exert the most substantial influence, followed by institutional governance‐related dimensions (control of corruption, rule of law) and, to a lesser extent, political institutions (political stability, voice, and accountability). Furthermore, institutional quality has a stronger positive effect on structural change in low‐income countries compared to middle‐income countries. These findings suggest that policymakers should prioritize enhancing institutional quality to drive structural transformation.